SUBSTRATE CHARACTERISTICS AND ITS IMPACT ON DISTRIBUTION OF MANGROVE SPECIES : A Case Study In Sungai Barong Kecil In The Sembillang National Park At Banyuasin, South Sumatra - Yuanita Windusari; Sarno Sarno; Edward Saleh; Laila Hanum (The East Java Biological Society, 2014)
The composition and density of vegetation in the mangrove areas affected soil conditions. Areas with a smooth distribution of substrat particles contain higher organic matter, and is characterized by the growth of mangrove better and more diverse. How environmental conditions affect the distribution of mangrove substrats observed in this study. The study was conducted in the area of Sungai Barong Kecil and Sungai Barong Besar which is part of the Sembilang National Park, Banyuasin District, South Sumatra. The study was conducted in May and June 2014. Location determined substrats by purposive sampling with particular consideration, and samples were taken using a modified PVC pipe at a depth of 10-30 cm, while the checkered line method with parallel lines used for observation shoreline mangrove distribution. Physical parameters such as salinity environmental chemistry, pH, and moisture. Analysis was performed on substrat particle size, substrat organic matter content, as well as the condition and type of mangrove. The results showed that the Sungai Barong Kecil area tend to have a much smoother distribution of substrat particles (clay content and higher dust). This leads to more easily grow mangroves and mangrove species were found to be more diverse (Avicennia marina, Avicennia alba, Rhizophora mucronata and Avicennia officianalis). Avicennia marina is the dominant species that indicates that the species is highly adaptable to various environmental conditions.